Stability and Compatibility Studies of Levothyroxine Sodium in Solid Binary Systems—Instrumental Screening - Ionuț Ledeți; Mirabela Romanescu; Denisa Cîrcioban; Adriana Ledeți; Gabriela Vlase; Titus Vlase; Oana Suciu; Marius Murariu; Sorin Olariu; Petru Matusz; Valentina Buda; Doina Piciu (Pharmaceutics, 2020)
The influence of excipients on the stability of sodium levothyroxine pentahydrate (LTSS) under ambient conditions and thermal stress was evaluated. Since LTSS is a synthetic hormone with a narrow therapeutic index, the interactions of LTSS with excipients can lead to a drastic diminution of therapeutic activity. Ten commonly used pharmaceutical excipients with different roles in solid formulations were chosen as components for binary mixtures containing LTSS, namely, starch, anhydrous lactose, D-mannitol, D-sorbitol, gelatin, calcium lactate pentahydrate, magnesium stearate, methyl 2-hydroxyethyl cellulose (Tylose), colloidal SiO2 (Aerosil) and talc. As investigational tools, universal attenuated total reflectance- Fourier transform infrared spectroscopy UATR-FTIR spectroscopy and thermal analysis were chosen and used as follows: UATR-FTIR spectra were drawn up for samples kept under ambient conditions, while thermoanalytical tools (TG/DTG/HF data) were chosen to evaluate the inducing of interactions during thermal stress. The corroboration of instrumental results led to the conclusion that LTSS is incompatible with lactose, mannitol and sorbitol, and these excipients should not be considered in the development of new generic solid formulations.